A Survey from a Large Academic Medical Center - Ellsworth, M.A.; Homan, J.M.; Cimino, J.J.; Peters, S.G.; Pickering, B.W.; Herasevich, V. (Applied Clinical Informatics, 2015)
Objective: To better understand the literature searching preferences of clinical providers we conducted an institution-wide survey assessing the most preferred knowledge searching techniques.Materials and Methods: A survey regarding literature searching preferences was sent to 1862 unique clinical providers throughout Mayo Clinic. The survey consisted of 25 items asking respondents to select which clinical scenarios most often prompt literature searches as well as identify their most preferred knowledge resources.Results: A total of 450 completed surveys were returned and analyzed (24% response rate). 48% of respondents perform literature searches for more than half of their patient interactions with 91% of all searches occurring either before or within 3 hours of the patient interaction. When a search is performed 57% of respondents prefer synthesized information sources as compared to only 13% who prefer original research. 82% of knowledge searches are performed on a workstation or office computer while just 10% occur on a mobile device or at home.Conclusion: Providers in our survey demonstrate a need to answer clinical questions on a regular basis, especially in the diagnosis and therapy domains. Responses suggest that most of these searches occur using synthesized knowledge sources in the patient care setting within a very short time from the patient interaction.Citation: Ellsworth MA, Homan JM, Cimino JJ, Peters SG, Pickering BW, Herasevich V. Point-of-care knowledge-based resource needs of clinicians: A survey from a large academic medical center. Appl Clin Inf 2015; 6: 305–317http://dx.doi.org/10.4338/ACI-2014-11-RA-0104
Keywords: Electronic health records; evidence-based medicine; information storage and retrieval; point of care technology; user-computer interface